PERGESERAN TATA CARA PERNIKAHAN ADAT JAWA YOGYAKARTA DI KECAMATAN TAPUNG KABUPATENKAMPAR - Fifit Fitriani; Hambali Hambali; Haryono Haryono (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This research is motivated by a shift in Javanese traditional marriage in Yogyakarta in the District of Tapung in the Kampar District in the manner in which the marriage is conducted. The formulation of the problem of this research is "What aspects have changed in the Javanese Customary Marriage Procedure in the District of Tapung Kabuapten Kampar", "What factors influence changes in the procedures for traditional Javanese marriage in the District of Tapung Kabuapten Kampar". The purpose of this study was to find out what aspects were changed in the customary Javanese marriage procedures in the District of Tapung Kabuapten Kampar. Data collection techniques in this study were observation, interviews and documentation. The research respondents took 5 informants, from community informants representing the community in Tapung District, Kampar Regency. Data analysis techniques in this study used descriptive qualitative methods. The results of the study prove that there was indeed a change in several stages of the event being held such as: the preparatory stage before the wedding, the implementation stage which was previously carried out in detail, but now people prefer to carry out events that are considered important. This is influenced by several factors such as: internal factors namely invention (new discoveries), increasing and decreasing population. The external factor is the influence of other people's culture.Key Words: Shifting, Traditional Marriage, Javanese Yogyakarta Community